TELAAH KURIKULUM BAHASA ARAB DI MA AL-HIDAYAH DEPOK - Perwira, Agung; Faridah, Eva Siti; apriliani, putri; Mubarok, Ananda Miftahul (JURNAL KAJIAN ISLAM MODERN, 2023)
Arabic language learning is a provision of knowledge to students, namely with active and passive oral language skills, as well as good writing. The purpose of learning Arabic is for students to be able to master Arabic covering four skills, namely listening, speaking, reading, and writing. The method used qualitative Case Study approach is research on events that have occurred without researchers doing any intervention. The research was conducted on grade 10 Arabic learning at Madrasah Aliyah Al-Hidayah Depok Where. Data collection method by conducting interviews, observation and documentation. Data analysis techniques with data reduction, by correcting (researching) and explaining (decrypting), are finally described in the form of a script. Results of an interview with your Arabic teacher. H. Syamsul Hadi S.Pd that the strategies used in overcoming students to be interested in following language learning . Keyword : Arabic language curriculum